Customer dependence on OTA, brand autonomy, and direct booking intention in Bali boutique villas - Karidhana, I Wayan Aditya Siddhanta; Padmalia, Metta (Manajemen dan Bisnis, 2026)
This study examines the influence of customer dependence on Online Travel Agents (OTAs) on brand autonomy perception and direct booking intention in boutique villas in Bali. Grounded in the Stimulus–Organism–Response (S-O-R) framework, OTA dependence is positioned as the external stimulus, brand autonomy perception as the internal evaluative mechanism, and direct booking intention as the resulting behavioral response. Using a quantitative approach, data were collected from 192 international and domestic travelers who had booked boutique villas via OTA platforms or direct channels. Structural Equation Modeling–Partial Least Squares (SEM–PLS) was employed to analyze both direct and mediating effects. The findings reveal that OTA dependence significantly diminishes brand autonomy perception and reduces customers’ intention to book directly. Brand autonomy perception positively influences direct booking intention and acts as a significant mediator in the relationship between OTA dependence and direct booking behaviors. These results highlight the strategic necessity for boutique villas to strengthen direct digital channels and reinforce authentic brand narratives to counterbalance OTA standardization. In experiential destinations such as Bali, enhancing brand autonomy is essential to maintain differentiation, improve customer trust, and support sustainable distribution strategies.